Exploring the modulatory impact of isosakuranetin on Staphylococcus aureus: Inhibition of sortase A activity and α-haemolysin expression - Lili Tian; Li Wang; Fengying Yang; Tiezhong Zhou; Hong Jiang (Virulence, 2023)
ABSTRACTThe ubiquity of methicillin-resistant Staphylococcus aureus (MRSA) and the mounting prevalence of antibiotic resistance necessitate the identification of novel therapeutic approaches to reduce the selective pressure of antibiotics. Targeting bacterial virulence factors, such as the pivotal Sortase A (SrtA) in S. aureus for adhesion and invasion, and the salient toxin α-Hemolysin (Hla), offers a sophisticated approach to attenuate pathogenicity without bacterial elimination. Herein, we report the discovery of a flavonoid, isosakuranetin, which inhibits the activity of S. aureus SrtA. A fluorescence resonance energy transfer assay revealed that isosakuranetin exhibited a low IC50 of 21.20 μg/mL. Furthermore, isosakuranetin significantly inhibited SrtA-related virulence properties, such as bacterial adhesion to fibrinogen, biofilm formation, and invasion of A549 cells. We employed fluorescence quenching and molecular docking to determine the interactions between isosakuranetin and SrtA, revealing the key amino acid sites for binding. Importantly, isosakuranetin inhibited the haemolytic activity of S. aureus in vitro at a concentration of 32 μg/mL. Moreover, isosakuranetin effectively suppressed the transcription and expression of Hla in a dose-dependent manner and regulated the transcription of RNAIII, the upstream operator of Hla. Notably, isosakuranetin demonstrated in vivo efficacy in a mouse model of S. aureus-induced pneumonia by significantly improving survival rates and reducing lung damage. This is a valuable finding, as isosakuranetin’s dual inhibitory effects on SrtA and haemolytic activity, as well as its anti-virulence activity against MRSA, make it an excellent candidate for therapeutic development.